Poetics in Museological Crossroads: Nosso Sagrado, enchantment and the passage of time - Pedro Marco Gonçalves; Arantxa Ciafrino (Museum, Materials and Discussions)
The article examines the processes of musealization and re-musealization of the Coleção do Nosso Sagrado, a collection of sacred objects that narrates a history of religious oppression in Brazil within a colonial context. An analysis of three specific pieces and their custodial processes at the Museu da República, managed in shared custody with researchers and religious leaders, serves as a case study for a critical, decolonial, and reparative museology.